The challenges of teaching mathematics in the context of the COVID-19 pandemic: a look at youth and adult education (Research, Society and Development, 2022)
Youth and Adult Education (YAE) promotes the achievement of knowledge and the inclusion of individuals who have not completed their studies in the regular period, promoting their insertion in the educational field. The present study aimed to reflect on the difficulties faced during remote teaching in the modality of EJA, specifying the educational aspects referring to the teaching of mathematics and the challenges that arose in the context of the COVID-19 pandemic, in the eyes of the students and the mathematics teacher. The research, of qualitative approach, counted in its methodological organization with a literature review, contemplating aspects related to the legislation and norms that govern EJA, relating them to the teaching of mathematics, as well as the thought and contributions of the educator Paulo Freire. As an instrument of data collection, we chose to apply a questionnaire through Google Forms, having as participants 10 EJA students from Cycle IV (Elementary School) and the mathematics teacher of the respective class. In the analysis, the difficulties and the need for a transformation in the training process were highlighted, associating teaching and learning in the development and construction of a solid, innovative education, aiming at the formation of critical citizens who are aware of their actions.